Antifungal potential and fatty acid profile of two Jatropha curcas (Euphorbiaceae) oils - Hemayoro Sama (Elsevier, 2021)
This study investigated the anti-fungal activities and the fatty acids composition of two oil samples of Jatropha. Seeds collected from two different agro climatic localities were used for oil extraction. These oils at the 1% and 2% concentrations were tested on Fusarium solani strains isolated from tomato plants against negative and positive controls. The fatty acids composition was analyzed by GC-MS. The results showed that, at all concentrations, both oils showed growth inhibition and sporulation reduction depending on the oil. Calthio C, used as positive control showed complete inhibition of mycelial growth and sporulation while sterile water, the negative control showed no growth inhibition. The 2% concentration of oil in sample 2 recorded the best inhibition rate (72.7%) while the lowest (34.5%) was recorded with the 1% concentration of oil in sample 1. The sample 1 oil and the sample 2 oil presented 45 and 51% sporulation inhibition respectively. In addition, the 2% concentration of Jatropha seeds oils from both agroclimatic zones showed a slightly higher inhibition than the 1% concentration. GC analysis revealed that both oil samples were predominantly unsaturated and had a variable fatty acid composition depending on the oil. The most important ones were vaccenic (50.18%), nonadecanoic (26.95%) and palmitic (12.87%) acids for sample 1 and linolelaidic (49.04%), nonadecanoic (25.7%) and palmitic (15.11%) acids for sample 2. Sample 1 had 11 fatty acids compared to 18 for sample 2. Both samples also had 9 identical fatty acid structures. Some of these fatty acids are known for their antimicrobial activity. Compared to sample 1, oil sample 2 also showed 7 additional fatty acids such as myristic and erucic acids. The activity of the oil is depended on the origin and fatty acid composition of the oils. Results study suggest that the samples are promising sources of natural antifungal.